Evaluation of the impact of transient interruption of antiangiogenic treatment using ultrasound-based techniques in a murine model of hepatocellular carcinoma - Marinelli, Sara (BioMed Central, 2014)
BACKGROUND: Development of escape pathways from antiangiogenic treatments was reported to be associated with enhanced tumor aggressiveness and rebound effect was suggested after treatment stop. Aim of the study was to evaluate tumor response simulating different conditions of administration of antiangiogenic treatment (transient or definitive treatment stop) in a mouse model of hepatocellular carcinoma. METHODS: Subcutaneous tumors were created by inoculating 5×10(6) Huh7 cells into the right flank of 14 nude mice. When tumor size reached 5–10 mm, mice were divided in 3 groups: group 1 was treated with placebo, group 2 was treated with sorafenib (62 mg/kg via gavage) but temporarily suspended from day +5 to +9, whereas in group 3 sorafenib was definitively stopped at day +5. At day +13 all mice were sacrificed, collecting masses for Western-Blot analyses. Volume was calculated with B-mode ultrasonography at day 0, +5, +9, +11 and +13. VEGFR2-targeted contrast-enhanced ultrasound using BR55 (Bracco Imaging) was performed at day +5 and +13 and elastonosography (Esaote) at day +9 and +11 to assess tumor stiffness. RESULTS: Median growth percentage delta at day +13 versus day 0 was 197% (115–329) in group 1, 81% (48–144) in group 2 and 111% (27–167) in group 3. Median growth delta at day +13 with respect to day +5 was 79% (48–127), 37% (−14128) and 81% (15–87) in groups 1, 2 and 3, respectively. Quantification of targeted-CEUS at day +13 showed higher values in group 3 (509 Arbitrary Units AI, range 293–652) than group 1 (275 AI, range 191–494) and group 2 (181 AI, range 63–318) (p = 0.033). Western-Blot analysis demonstrated higher VEGFR2 expression in group 3 with respect to group 1 and 2. CONCLUSIONS: A transient interruption of antiangiogenic treatment does not impede restoration of tumor response, while a definitive interruption tends to stimulate a rebound of angiogenesis to higher level than without treatment.